Legal Implications of Civil and Criminal Law on Investment Fraud Under the Guise of Online Business - Moh. Ja’far Sodiq Maksum (Indonesian Economic Review, 2024)
The development of digital technology has opened new opportunities in online platform-based investments, but it has also increased the risk of fraud disguised as legal businesses. The prevalence of online investment fraud in Indonesia shows that national laws have not fully been able to respond to the complexity of increasingly sophisticated and cross-border digital crimes. This study aims to examine the legal implications, both civil and criminal, of online investment fraud practices and to propose an integrative and adaptive legal approach. The method used is Systematic Literature Review (SLR), by reviewing scientific articles, regulations, and relevant court decisions from 2014 to 2024, based on the PRISMA stages. Research findings indicate that perpetrators employ various modalities such as Ponzi schemes, illegal MLM, and cryptocurrency manipulation, targeting communities with low legal literacy. From the civil perspective, challenges arise regarding the validity of digital contracts and the execution of compensation, while from the criminal perspective, proving elements of fraud and tracking down offenders poses significant challenges. Additionally, the dualism of legal approaches weakens and makes victim protection ineffective. This study concludes that civil and criminal law must synergize through regulatory reform, strengthening institutions, and enhancing public legal literacy to ensure justice and security in digital investment. Legal reforms based on inter-institutional collaboration and responsive to digital dynamics are key to breaking the cycle of fraud that undermines public trust in the national legal and economic system.